Temporary cervical sling and uterine twist before B-Lynch for massive uterine bleeding after delivery - Basile Pache; Vincent Balaya; David Desseauve (Taylor & Francis Group, 2022)
AbstractMassive uterine bleeding occurring after delivery is in most cases unpredictable and can have fatal consequences. This article presents the technique of combining the twisting of uterus on a 90° rotation on its axis and positioning a sling around the cervix, allowing to decrease incoming blood flow from uterine and ovarian arteries. The aim of this easy-to-use procedure is to enable surgeons and anaesthesiologists to respectively ensure the presence of an experienced surgeon and to stabilise the haemodynamic of the patient. It is a modus operandi of particular interest in resources' challenged environments.